Sosialisasi Pentingnya Pengoptimalan Teknologi Tepat Guna Bagi Industri Produksi Pakan Udang dan Pakan Ikan - Robby, Ahmad Asrori Ainur; Junaidi, Muhammad Faisal; Usman, Mualifi (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service project aims to develop and optimize a plate cutting machine to support production process efficiency in the fish feed industry. The activity was carried out at an industry in Manyar District, Gresik Regency, East Java, as part of the implementation of the community service program. The methods used were design engineering and experimentation, supported by literature studies and direct dialogue with the community. The development results showed that modifying the machine from a manual to an automatic system successfully increased the speed, neatness, and effectiveness of plate cutting, thus contributing to increased productivity and supporting the transformation towards the development of appropriate technology.